The Models of Voids in the Friedman Universe - Korkina, M. P.; Turinov, A. N. (Одеські астрономічні публікації, 2017)
The astronomical observations of the last years show that there are the regions in the Universe with much lower density of matter, than their surroundings. Theoretical studies of the regions (voids) in the model of the expanding Universe are carried on different directions. In this paper the voids have been built by means of matching Tolman and Friedman solutions. The Lichnerovich-Darmois matching conditions are used. It is shown that in expanding Universe with at space the voids can not exist. So we have Friedman Universe with voids, with described by the Tolman solution. The models of voids in the Friedman Universe with negative spatial curvature have been built.